Government intervention need for social security improvement in the Democratic Republic of the Congo: A theoretical analysis using the principal-agent model - Didier Mumpambala Luzolo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
African populations need better support through social protection mechanisms. Among those who need social security are millions of older people who, having worked all their lives in the formal sector, are in precarious situations with lower benefits. This study aims to appreciate theoretically, using the principal-agent model, the need for government intervention as a way to improve social security in Democratic Republic of the Congo. The study reveals that the Congolese government as a principal can motivate the Institut National de Sécurité Sociale (National Social Security Institute, public company) as an agent by offering two types of contracts (optimal and sub-optimal) in order to increase Congolese pension income.
Keywords: H55; C61; D82; D86; 330; social security; pensions; contracts; principal-agent model; Institut National de Sécurité Sociale